Heat stress impairs centromere structure and segregation of meiotic chromosomes in Arabidopsis - Crhak Khaitova, Lucie; Mikulkova, Pavlina; Pecinkova, Jana; Kalidass, Manikandan; Heckmann, Stefan; Lermontova, Inna; Riha, Karel (eLife, 2024)
Heat stress is a major threat to global crop production, and understanding its impact on plant fertility is crucial for developing climate-resilient crops. Despite the known negative effects of heat stress on plant reproduction, the underlying molecular mechanisms remain poorly understood. Here, we investigated the impact of elevated temperature on centromere structure and chromosome segregation during meiosis in Arabidopsis thaliana. Consistent with previous studies, heat stress leads to a decline in fertility and micronuclei formation in pollen mother cells. Our results reveal that elevated temperature causes a decrease in the amount of centromeric histone and the kinetochore protein BMF1 at meiotic centromeres with increasing temperature. Furthermore, we show that heat stress increases the duration of meiotic divisions and prolongs the activity of the spindle assembly checkpoint during meiosis I, indicating an impaired efficiency of the kinetochore attachments to spindle microtubules. Our analysis of mutants with reduced levels of centromeric histone suggests that weakened centromeres sensitize plants to elevated temperature, resulting in meiotic defects and reduced fertility even at moderate temperatures. These results indicate that the structure and functionality of meiotic centromeres in Arabidopsis are highly sensitive to heat stress, and suggest that centromeres and kinetochores may represent a critical bottleneck in plant adaptation to increasing temperatures.
Keywords: histony; reakce na tepelný šok; Plants; centromera; gene expression; Arabidopsis; Centromere; Meiosis; centremeres; meiosis; chromosomes; centromeric histone; micronuclei; rostliny; meióza; segregace chromozomů; A. thaliana; Heat-Shock Response; kinetochory; Kinetochores; Histones; cell biology; Chromosome Segregation; spindle assembly checkpoint